Evaluation of Mechanical Properties of the Two PVC Conveyor Belts - Bojic, Nada; Nikolic, Ruzica; Banic, Milan; Hadzima, Branislav (Communications - Scientific Letters of the University of Zilina, 2018)
Conveyor belts with woven plastic belts, aimed for general applications, are very economical transporting means for longer distances. During the operation, the conveyor belts are subjected to various mechanical loadings. The consequences of those loadings are increased stretching of the belt and change of its tensile strength, which negatively affect the proper functioning of the transporter. To avoid the irregularities in the conveyor belt's operation, the tensile properties of the two plastic woven belts were tested (maximal force, maximal extension, breaking force and extension at break). In that way the conditions of the two belts were established. Based on performed experiments the belt that is more suitable for application in the transporter was defined.
Keywords: woven plastic belt; extension; tensile strength; conveyor belt